Comparative phytohormone pro les, lipid kinase and lipid phosphatase activities in barley aleurone, coleoptile, and root tissues - Meringer, Maria Veronica (2012)
We analyzed lipid kinase and lipid phosphatase activities and determined endogenous phytohormone levels by liquid chromatography–tandem mass spectrometry in root and coleoptile tissues following germination of barley (Hordeum vulgare) seeds. The enzymes showing highest activity in aleurone cells were diacylglycerol kinase (DAG-k, EC 2.7.1.107) and phosphatidate kinase (PA-k). The ratio of gibberellins (GAs) to abscisic acid (ABA) was 2-fold higher in aleurone than in coleoptile or root tissues. In coleoptiles, phosphatidylinositol 4-kinase (PI4-k, EC 2.7.1.67) showed the highest enzyme activity, and jasmonic acid (JA) level was higher than in aleurone. In roots, activities of PI4-k, DAG-k, and PA-k were similar, and salicylic acid (SA) showed the highest concentration. In the assays to evaluate the hydrolysis of DGPP (diacylglycerol pyrophosphate) and PA (phosphatidic acid) we observed that PA hydrolysis by LPPs (lipid phosphate phosphatases) was not modified; however, the diacylglycerol pyrophosphate phosphatase (DGPPase) was strikingly higher in coleoptile and root tissues than to aleurone. Relevance of these findings in terms of signaling responses and seedling growth is discussed.